Review of the role of gastrointestinal multiplex polymerase chain reaction in the management of diarrheal illness. Issue 12 (23rd June 2021) - Teh, Readon; Tee, Wei De; Tan, Eunice; Fan, Kristie; Koh, Calvin Jianyi; Tambyah, Paul Ananth; Oon, Jolene; Tee, Nancy; Soh, Alex Yu Sen; Siah, Kewin Tien Ho
Abstract: Acute and chronic diarrheal illness secondary to gastrointestinal infection is a significant cause of morbidity and mortality around the world. A cornerstone of management includes prompt diagnosis and appropriate treatment of culprit pathogens. Timely diagnosis can improve patient care, assist in infection control, and prevent disease outbreaks. Historical methods of diagnosis include traditional culture methods and stool analysis. These are limited by long turnaround time and inability to simultaneously assess multiple pathogens. The advent of multiplexed nucleic acid amplification tests first began with the Food and Drug Administration‐approved respiratory virus multiplex polymerase chain reaction (PCR) panel in 2009, followed by gastrointestinal infections in 2013, and neurological infections in 2014. We conducted a review of current literature pertaining to the clinical utility of a gastrointestinal multiplex PCR in management of acute and chronic diarrhea in patients. To date, seven platforms approved by the US Food and Drug Administration are used in detection of various bacterial, viral, and parasitic causative organisms for diagnosis of gastrointestinal infections. The sensitivity and specificity of each assay vary depending on the tested organism. Interpretation of a positive result has to be tailored to the clinical context. Further studies are required to establish the utility of gastrointestinal multiplex PCR from a cost‐based perspective, whether specific enteropathogens such as Clostridioides difficile are better assessed with toxin gene detection and whether new parameters such as cycle threshold values can improve clinical application of test results.